2001
DOI: 10.1038/sj.bmt.1703054
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions to enhance transfection of human CD34+ cells by electroporation

Abstract: Summary:The ability to culture CD34 + stem cells, while maintaining their pluripotency, is essential for manipulations such as gene transfection for therapeutic trials. Human peripheral blood (PB) CD34 + cells (у90% purity) were cultured for up to 4 days in serum-free culture medium supplemented with thrombopoietin (TPO), stem cell factor (SCF),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
0
18
1
Order By: Relevance
“…13 Here, we hypothesize that the interaction between VCAM-1 and/or fibronectin, expressed and/or secreted by osteoblasts, and the VLA-4 integrin, expressed on HPCs, may provide a prosurvival signal for UCB-HPCs exposed to low O 2 . To test this, we plated freshly isolated UCB-CD34 ؉ progenitors onto poly-lysine (PLL)-, VCAM-1-, or fibronectin (FN)-coated plates in the presence of a cytokine cocktail (SCF ϩ FLT3L ϩ TPO), shown previously to be optimal for HPC cultures 21 ; the plates were then immediately placed in a 20% ( Figure 1A left) or 2% to 3% (Figure 1A middle) O 2 environment, and cell death was assessed after 48 hours. Compared with 20% O 2 culture, we observed a more than 2-fold increase in cell death in 2% to 3% O 2 culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Here, we hypothesize that the interaction between VCAM-1 and/or fibronectin, expressed and/or secreted by osteoblasts, and the VLA-4 integrin, expressed on HPCs, may provide a prosurvival signal for UCB-HPCs exposed to low O 2 . To test this, we plated freshly isolated UCB-CD34 ؉ progenitors onto poly-lysine (PLL)-, VCAM-1-, or fibronectin (FN)-coated plates in the presence of a cytokine cocktail (SCF ϩ FLT3L ϩ TPO), shown previously to be optimal for HPC cultures 21 ; the plates were then immediately placed in a 20% ( Figure 1A left) or 2% to 3% (Figure 1A middle) O 2 environment, and cell death was assessed after 48 hours. Compared with 20% O 2 culture, we observed a more than 2-fold increase in cell death in 2% to 3% O 2 culture.…”
Section: Resultsmentioning
confidence: 99%
“…We did not see a further reduction of cell death on FN, compared with VCAM-1, suggesting that VLA-4 engagement alone was sufficient for the prosurvival effect under 2% to 3% O 2 . We used fibronectin (FN) 21 as the ligand throughout the remaining part of the current studies.…”
Section: Resultsmentioning
confidence: 99%
“…CD34 ϩ cells were plated at a density of 0.4 ϫ 10 6 cells/ml in expansion media consisting of serum-free expansion medium (SFEM; StemCell Technologies) that was supplemented with 2% penicillin/streptomycin, recombinant human thrombopoietin (50 ng/ml), SCF (25 ng/ml), and Flt-3 ligand (50 ng/ml) (27). Media were changed when cell density reached 1 ϫ 10 6 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…83,84 Regarding the requirement for active cell cycling for efficient transfection via electroporation, existing data from cell synchronization experiments are controversial. 80,[85][86][87] Prestimulation of CD34 + cells with recombinant cytokines for various time intervals prior to electroporation has been shown to enhance transfection efficiency and this effect was attributed to the increase in the subpopulation of cells in S phase. 78,83 However, others demonstrated that stimulated and unstimulated CD34 + cells are transfected with equal efficiencies.…”
Section: 79-81mentioning
confidence: 99%